KEADILAN BAGI KONSUMEN: MEMBEDAH UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 8 TAHUN 1999 - Holijah, Holijah (Universitas Islam Negeri Raden Fatah Palembang, 2015)
Abstract: Ideologically the nation of Indonesia agreed to build alaws of the state based on Pancasila. It’s serve as the source ofall sources of law of Indonesian. The value of Pancasilaimplemented to all products of laws. This article will be studiedmore in depth about act - consumer protection perspective ofPancasila..ملخص: وافق أیدیولوجیا إندونیسیا لإقامة دولة القانون التي ھي الحال في دولتناالدستوریة الخاصة على أساس البانشاسیلا. البانشاسیلا تستخدم كمصدر لجمیعمصادر دولة القانون. یجب أن تكون القیم البانشاسیلا التلوین المھیمن أي منتجاتالقانونیة، سواء على مستوى المؤسسة وتنفیذ و الإنفاذ. من خلال ھذا المقال سوفتدرس أكثر في العمق عن وجھة نظر قانون حمایة المستھلك البانشاسیلا.Kata Kunci: Pancasila, Perlindungan Konsumen